Ensuring Indigenous cultural respect in Australian undergraduate nursing students. Issue 4 (7th June 2018) - Power, Tamara; Virdun, Claudia; Gorman, Edward; Doab, Anna; Smith, Rachel; Phillips, Angela; Gray, Joanne
ABSTRACT: Like other Westernised countries, Australia's history of colonisation, racism and oppression has impacted upon Indigenous Peoples' health and well-being. It is also evident that institutional racism and ongoing colonisation are present in the Australian health system. Better preparation of health professionals to work in a culturally respectful way can contribute to addressing health disparities and prejudices. One approach to enabling the development of cultural respect is through embedding an Indigenous graduate attribute (IGA) across curricula and ensuring the process is thoughtfully developed and assessed. This paper describes and discusses the process of developing an assessment criteria template (ACT) to assess Indigenous cultural respect in an undergraduate nursing degree programme. Critical to the project was meaningful engagement with Indigenous stakeholders and Indigenous leadership to inform the development and implementation process. Although the context will vary globally due to the diversity of Indigenous Peoples and each country's history of colonisation, by publishing this work, we intend to provide transparency into the process we undertook to embed and assess an IGA ACT in an undergraduate nursing curriculum. We hope this is helpful for other tertiary institutions internationally who are also engaging in this space.